Attenuation Levels of Lung Fields in Quantitative Computed Tomography Evaluation Are Associated With Overall Survival and the Incidence of Acute Exacerbation in Combined Pulmonary Fibrosis and Emphysema: A Single‐Center Retrospective Observational Study - Yusuke Suzuki; Yoshiaki Kitaguchi; Takumi Kinjo; Norihiko Goto; Masamichi Komatsu; Fumika Ueno; Yosuke Wada; Atsuhito Ushiki; Masanori Yasuo; Kiyoyasu Fukushima; Masayuki Hanaoka (Health Science Reports, 2026)
ABSTRACT Background and Aims Combined pulmonary fibrosis and emphysema (CPFE) is characterized by the coexistence of emphysematous lesions and fibrotic interstitial lung disease. We assessed the relationships of quantitative computed tomography (CT)‐derived measures with clinical characteristics and outcomes in CPFE. Methods At a single institution, 129 patients with CPFE were evaluated retrospectively. Baseline CT data were available for the entire cohort; 71 patients underwent repeat CT approximately 1 year later. The evaluated CT measures were low attenuation volume percentage (LAV%), high attenuation volume percentage (HAV%), diseased lung volume percentage (DLV%), erector spinae muscle cross‐sectional area (ESM CSA ), and the main pulmonary artery‐to‐aorta diameter ratio. Associations of baseline values and annualized changes with overall survival and acute exacerbation incidence were examined. Results None of the baseline quantitative CT measures was associated with the risk of death. In contrast, annualized changes in LAV%, HAV%, and DLV% were associated with the risk of death. Overall survival was shorter among patients with an annual DLV% increase of at least 1.5%. At baseline, HAV% and DLV% were associated with acute exacerbation incidence; in the longitudinal analysis, associations were observed for annualized changes in LAV%, HAV%, DLV%, and ESM CSA . Conclusion In CPFE, annualized changes in LAV%, HAV%, and DLV% were associated with mortality and acute exacerbation incidence in their respective models. An annual DLV% increase of at least 1.5% was associated with shorter overall survival. Quantitative CT attenuation indices can inform risk assessment in CPFE.